A knowledge-based approach to heart disease prevention in diabetes care - Hudiyawati, Dian; Widodo, Arif; Faozi, Ekan; Khairunisa, Septi; Saqina, Adhisty Fachrine Ayu (Universitas Muhammadiyah Magelang, 2025)
Diabetes Mellitus (DM) is a prioritized health issue in the Nusukan Public Health Center area and a major risk factor for heart disease. Surveys and discussions with health workers revealed that the Prolanis group had never undergone heart disease risk screening nor received education on heart disease prevention related to DM. This community service aimed to increase the knowledge of individuals with diabetes in preventing heart disease. The approach method of this activity was counseling on the implementation of self-management for individuals with diabetes mellitus. The evaluation results demonstrated a significant increase in participants' knowledge regarding chronic disease management, particularly DM self-management, as evidenced by the increase in average scores from the pre-test (68.04) to the post-test (88.53).